EFEKTIVITAS PELAYANAN PSIKOLOGIS TERHADAP LANJUT USIA (Studi Kasus Pada UPTD Pusat Pelayanan Sosial Lanjut Usia Mappakasunggu Parepare) - Andriani B; Muhammad Saleh; Iskandar Iskandar (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
This research is qualitative descriptive by conducting interviews, observing and documenting to produce descriptive data in the form of words, written, or oral, and observed behavior. The results showed that 1) the elderly background had a glorious period of employment status as soldiers, civil servants and field tennis athletes, but with neglected and vulnerable conditions they experienced so they could prevent their psychological state. 2) Forms of services used in psychological services in the elderly in the form of group counseling and therapy with spiritual guidance which is a process carried out through Islamic psychotherapy, and mental fitness therapy and skill guidance. 3) The effectiveness of psychological services is said to be effective seeing from the effectiveness theory which shows the success in terms of achieving the target actions which are determined by meeting the needs of abraham maslow needs with the results that the elderly feel more secure and comfortable with holding consultations every day, feeling more cared for by mentoring from the coach who always visit their guesthouse, feel more self-respect because they are still able to do gymnastic activities and skill guidance, and with spiritual guidance can give them inner peace and bring closer to Allah SWT. Thus, it can be concluded that the effectiveness of psychological services in the UPTD of the elderly social service center, while waiting for Parepare to be effective, has seen from the benchmark of the theory of effectiveness and the fulfillment of elderly needs that they feel more comfortable in their homes than in their own homes. However, it is still less effective when viewed in terms of group consultation and therapy room facilities, as well as limited therapeutic equipment.